Laparoscopic cornuotomy for interstitial pregnancy and postoperative course. Issue 8 (August 2014) - Watanabe, Tadashi; Watanabe, Zen; Watanabe, Takanori; Fujimoto, Kumiko; Sasaki, Etsuko
Abstract Aim The aim of this study was to evaluate the advantages of laparoscopic cornuotomy in treating interstitial pregnancy, and the effect of the procedure on reproductive outcomes. Methods Thirteen patients were treated for interstitial pregnancy by laparoscopic cornuotomy with or without local methotrexate injection, between March 2000 and January 2012 at NTT East Japan Tohoku Hospital and Sendai City Hospital. The patients were followed to assess the outcomes of subsequent pregnancies for at least 1 year after the operation. Results All 13 cases of interstitial pregnancy were successfully treated by laparoscopic cornuotomy, without performing cornual resection or laparotomy. The mean gestational age was 7.6 ± 1.3 weeks, and the average serum hCG level was 20 800 ± 18 100 IU/L. The mean cornual mass size was 34.6 ± 10.2 mm. Eight of the patients later obtained a spontaneous intrauterine pregnancy. Three patients that delivered by cesarean section showed no uterine dehiscence or thinning of the scar at the site of the earlier cornual incision and repair. None of the patients experienced uterine rupture. Conclusion Interstitial pregnancy can be selectively treated by laparoscopic cornuotomy with local methotrexate injection, if managed carefully.